Premenstrual syndrome and premenstrual dysphoric disorder: Symptoms severity, functional impairment, and associated factors: A Saudi cross-sectional study - Samiha Hamdi Sayed; Mohammed AL-Mohaithef; Enas Mohamed Ibrahim; Ebtesam A. Elsayed (Journal of Education and Health Promotion)
BACKGROUND: Premenstrual syndrome (PMS) is a considerable health problem among women that negatively impacts their functionality and productivity. Thus, this study aims to assess PMS and premenstrual dysphoric disorder (PMDD) symptoms severity, functional impairment, and associated factors in Saudi Arabia. MATERIALS AND METHODS: A cross-sectional social media-based survey using a convenience sample of 623 Saudi women. A self-administered questionnaire was used, including the Personal Characteristics and Menstrual History Questionnaire and the Premenstrual Symptoms Screening Tool for Clinicians using the International Disease Classification System (DSM-IV) diagnostic criteria and The American College of Obstetricians and Gynecologists. Accordingly, women were classified into four PMS groups based on the severity of the symptoms. RESULTS: In total, 63.6% of the women had clinically significant PMS, 21.8% had mild PMS, 12.2% had PMDD, and only 2.4% had no PMS. Most PMS symptoms were moderate or severe, predominating affective symptoms (e.g., mood swings, feeling tearful, irritability, low self-identity, depressed mood). Statistically significant differences were observed between the PMS groups concerning the weighted mean scores of the affective and somatic symptoms and functional impairment, where the mean scores of all PMS symptoms were higher among PMDD followed by CSPMS than the mild and no PMS groups (P < 0.01). The functional impairment showed a significantly positive and higher correlation with affective than somatic symptoms (P = 0.000). Significant differences were detected between the PMS group based on the duration of menstrual flow (P = 0.034) and the number of pads per menstruation (P = 0.042). However, they had no significant differences based on personal characteristics (P > 0.05). CONCLUSION: PMS is a predominant health concern in Saudi Arabia, where the moderate to severe form is the most typical with an unneglected percentage of PMDD that affects women’s productivity. Thus, the Saudi government should focus on PMS, establishing health services and community-based PMS screening and counseling services.